2022
DOI: 10.1039/d2nr03050k
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of magic cube-like Ce-MOF-derived Pt/CeO2 catalysts for formaldehyde oxidation

Abstract: Controllable synthesis of MOFs with desired structures is of great significance to deepen the understanding of its crystal nucleation-growth mechanism and deliver unique structural features to their derived metal oxides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…2D, the peaks observed reveal that the existing forms of the Pt NPs in Pt/AT-CTF-1 were Pt 2+ , Pt 4+ and Pt 0 . 46 Based on these results, we demonstrated that the alkali treatment induced cyanohydrolysis in CTF-1 to generate the –COOH group, which acts as the in situ growing point to selectively anchor the Pt NPs.…”
Section: Resultsmentioning
confidence: 79%
“…2D, the peaks observed reveal that the existing forms of the Pt NPs in Pt/AT-CTF-1 were Pt 2+ , Pt 4+ and Pt 0 . 46 Based on these results, we demonstrated that the alkali treatment induced cyanohydrolysis in CTF-1 to generate the –COOH group, which acts as the in situ growing point to selectively anchor the Pt NPs.…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, v 0 , u 0 , v 2 , and u 2 are the characteristic peaks of Ce 3+ , while v 1 , v 3 , v 4 , u 1 , u 3 , and u 4 prove the existence of Ce 4+ . 37,38 As shown in Fig. 3e, the Ni 2p spectrum with a binding energy at 852.87 eV ( p 0 ) is attributed to the metal Ni.…”
Section: Resultsmentioning
confidence: 88%
“…The spectral curves of Pt/CeO 2 (MOF) and the other control catalysts have significant signals at 3648, 2950, 2865, 2736, 2073, 1652, 1575, 1373 and 1075 cm À1 . Among them, the bands at 2950, 2865, 2736 and 1075 cm À1 are assigned to C-H vibration of adsorbed HCHO, the bands at 3648 cm À1 are attributed to OH groups or adsorbed H 2 O on the catalyst surface, 1575 and 1373 cm À1 are ascribed to the vas(COO À ) of formate, and 2073 cm À1 is assigned to linearly adsorbed CO. 51 The appearance of these signals illustrates that the oxidation of HCHO on Pt/CeO 2 (MOF) is performed through two intermediates, formate and CO, identical to the typical HCHO oxidation process. 8,52 Besides the signals of the above species, the DRIFT spectrum of the Pt/CeO 2 (MOF) catalyst lacks a signal peak at 1320 cm À1 compared with those of the control catalysts, which corresponds to the C-O bond vibration of DOM.…”
Section: Reaction Mechanismmentioning
confidence: 93%